ANALISIS PENGARUH KAMPANYE BOIKOT PRODUK KFC TERHADAP RETURN SAHAM PADA PT FAST FOOD INDONESIA TBK - Indika Nurul Aulia; Aswar Anwar; Nur Afiah (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyze the effect of the KFC product boycott campaign on the stock returns of PT Fast Food Indonesia Tbk before and after the issuance of MUI Fatwa Number 83 of 2023 on November 8, 2023, as the t-0 event date. The variables of this study are the boycott campaign and stock returns before and after the issuance of MUI Fatwa Number 83, measured using a periodic data approach. The population of this study is the entire stock price of PT Fast Food Indonesia Tbk (IDX: FAST) listed on the Indonesia Stock Exchange, while the sample is the weekly closing price before and after the t-0 event with an observation time window of t-40 to t+40, t-30 to t+30, t-20 to t+20, t-10 to t+10 taken by time-series sampling. Data collection was carried out using documentation techniques. Data analysis was carried out using descriptive statistical tests, data normality test, paired sample t-tests, and Wilcoxon signed rank tests. The results of this study found no significant difference (<0.05) over the entire observation period, thus rejecting the hypothesis. This means that the boycott campaign had no effect on stock returns before and after the issuance of MUI Fatwa Number 83 of 2023. Keyword: Boycott, Stock Return, PT Fast Food Indonesia Tbk